The arrangement of Psalms 3-8 - Smith, Kevin G.; Domeris, William R. (Old Testament Essays, 2010)
An exhaustive analysis of Psalms 3-8 suggests that the editors of the Psalter juxtaposed psalms on the basis of link words. The headings and verbal links suggest that Psalms 3 and 7 belong together, as do Psalms 4-6. In this article, we propose that the editors formed this collection by inserting Psalms 4-6 between Psalms 3 and 7, which were neighbours in another collection. The strong verbal links between Psalms 3 and 4 provide the rationale for this merger. They then rounded off this miniature collection by joining Psalm 8 to Psalm 7, based on the hook word ''name.''
free
Keywords: SATS